Dimensional Changes of Lumbar Intervertebral Foramen in Direct Anterior Approach‐Specific Hyperextension Supine Position - Ming‐yang Liu (Orthopaedic Surgery, 2020)
Objective To investigate the changes in the lumbar intervertebral foramen (LIVF) dimensions from neutral supine to direct anterior approach (DAA)‐specific hyperextension supine position through a standardized three‐dimensional (3D) reconstruction computerized tomography (CT) method. Methods A total of 35 healthy volunteers (18 men and 17 women) were included in this retrospective study. The mean age of enrolled subjects was 28.9 ± 5.0 years. In September 2018, all the individuals underwent a 3D CT scan of the lumbar spine in neutral and 30° hyperextension supine positions, which mimicked the patient’s position in DAA total hip arthroplasty (THA). The dimensions of the LIVF, including foraminal area, height, and width, were measured on 3D reconstructed CT models at all lumbar foraminal levels. Foraminal area was defined as the area bounded by the adjacent superior and inferior vertebral pedicles, the posterosuperior boundary of the inferior vertebral body, the surface of the intervertebral disc posteriorly, the posteroinferior boundary of the superior vertebral body, and the surface of the ligamentum flavum anteriorly. Foraminal height was defined as the longest distance between the border of the superior and the inferior pedicle. Foraminal width was defined as the shortest distance between the posteroinferior edge of the superior vertebrae and the opposing boundary. Subgroup analysis and multiple linear regression were used to evaluate the relationship between percentage changes of the LIVF dimensions and side, sex, and age. Results The LIVF dimensions varied significantly between the two positions at all levels (P < 0.05). From neutral to hyperextension supine position, the foraminal area reduced by 20.1% at lumbar 1–2 (L1–2), 22.6% at L2–3, 19.9% at L3–4, 18.1% at L4–5, and 12.0% at lumbar 5–sacral 1 (L5–S1) level, respectively; the foraminal height reduced by 9.5% at L1–2, 10.5% at L2–3, 9.5% at L3–4, 9.6% at L4–5, and 6.1% at L5–S1 level, respectively; the foraminal width reduced by 12.8% at L1–2, 14.5% at L2–3, 13.0% at L3–4, 10.4% at L4–5, and 8.4% at L5–S1 level, respectively. The changes in LIVF dimensions were biggest at L2–3 level and smallest at L5–S1 level. Subgroup analysis showed that there were no significant differences in the percentage changes of LIVF dimensions between the sexes and sides (P > 0.05). Multiple linear analysis showed that the percentage changes of LIVF dimensions were not related to side, sex, and age (P > 0.05). Conclusion The dimensions of the LIVF showed significant decrease at all levels in the DAA‐specific hyperextension supine position compared with the neutral supine position, and the percentage changes of LIVF dimensions were not influenced by side, sex, and age.